Sistem Rekomendasi Jurusan Kuliah dalam Pengambilan Keputusan Menggunakan Metode MOORA - Ade Rizka; Ranti Eka Putri; Yanti Yusman; Maulana Fajar (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The dependence of the current generation Z on technology is a momentum to develop technological facilities in various aspects of life. In the educational aspect, it is important to take advantage of technological facilities by implementing systems and methods to provide maximum results. The level of education has several stages that have different concentrations and are increasingly conical. SMK students often experience difficulties or obstacles in choosing a college major. This is because students focus more on popular majors, even though there is a possibility that these majors are not appropriate. The research uses the MOORA method to help provide alternative recommendations for majors based on criteria of knowledgeability, skills ability, professional interest, object interest, and talent in decision-making. The MOORA method processes criteria optimally with rules that are appropriate to the problem and data. Alternative college majors based on 14 choices of college majors. The results of the MOORA method research based on alternative data on college majors that match the criteria can provide recommendations for college majors that Panca Budi Vocational School (STM) students can choose to continue their education in tertiary institutions. System testing produces an alternative with the largest y value, namely 31.2 for the Law major. The alternative with the largest y value will be the system's recommended alternative. The recommendation system for college majors can overcome difficulties or obstacles for students in choosing a college major, thus facilitating the lecture process because students can focus more on studying.